Revisiting UTAUT: Coordination Capability and Emotional Intelligence in Public Sector Innovation Performance - Tien Yustini; Hendry Wijaya; Akhmad Ghozali; Muhammad Wadud (Penerbit Goodwood, 2026)
Purpose: This study extends the Unified Theory of Acceptance and Use of Technology by examining how digital adoption influences public sector innovation performance, with coordination capability and emotional intelligence as key enabling mechanisms. Research Methodology: A quantitative explanatory design was employed using survey data collected from civil servants in a regional government institution that implemented electronic performance management. The model combines technology acceptance constructs with emotional intelligence, coordination skills, education, and work experience. Data were analysed using structural equation modelling to test the proposed relationships Results: Digital system acceptance improves employee performance, and this effect is strengthened by the coordination capability and emotional intelligence. Education and experience indirectly enhance outcomes by fostering adaptive behaviors. These findings extend the UTAUT by showing that the impact of technology performance depends on complementary human capabilities. Conclusions: Digital adoption enhances public sector performance only when it is supported by coordination capability and emotional intelligence. Therefore, digital transformation should be accompanied by human capability development and not merely technology implementation. Limitations: This study focused on a single local government context, limiting generalizability. Future research should compare multiple administrative levels and institutional settings to validate models across governance systems. Contributions: Public organizations should pair digital governance with interpersonal and coordination skill development to maximize electronic performance management benefits.